Automatic solar power for feeding system for aquaphonic farming - Muhamad Firdaus, Zaini (2013)
The objectives of this thesis are to design and fabricate a low cost and longer life span automatic fish feeder. Besides that, another objective of this project is to use the programmable interface controller (PIC) as a controller to control the machine. This automatic fish feeder is designed to dispense food into the aquarium at a particular time each day. The components for the developed machine can be divided into two types which are automation blocks and mechanical parts. Automation blocks components includes a DC motor, limit switch, relays and a PIC controller. The mechanical parts include auger bit and also the mechanical structure of the machine. An automatic device to feed fish at predetermined amounts of food and time. Fish feeder combines mechanical and electrical system to control fish feeding activity. This device consists of pellet tank, distributor and a stand. The dispensed food will be controlled by a motor which situated under the tank. A propeller design that differs by angle of force applied to spread the food, will distribute the pellet onto tank. A control system attached to this device allows the fish to be fed atmpredetermined food amount and time. Timer is used to control the motor which run the auger bit and propeller to increase functional efficiency. In this project, concepts are generated through the research on the existing patents to improve its limitations. A rotational movement of auger bit cause the food container rotates and dispenses the food from a small hole. The fish feeder is successfully fabricated and tested. Feeding can be done at predetermined interval of time and accurate amount of food is obtained. Furthermore the waste of fish food in pond is reduced efficiently. Results show that the machine would be able to feed the fish at a certain time range which is being set by the user using the built-in timer in the PIC controller. Besides that, one of the main future developments is to network the whole system which means by combining a few PICs and controlling them from only one control center. As a conclusion, this project is quite successful because it is able to fulfill all of the objectives stated and also performing up to expectation.